2020
DOI: 10.1101/2020.02.18.941856
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut eukaryotic communities in pigs: diversity, composition and host genetics contribution

Abstract: AbstractThis study aims to characterize commensal fungi and protists inhabiting the gut of healthy pigs, and explore the putative host genetic control over diversity and composition of pig gut eukaryotes. Fecal fungi and protists communities from 514 Duroc pigs of two sexes and two different ages were characterized by 18S and ITS ribosomal RNA gene sequencing. The gut mycobiota was dominated by yeasts, with a high prevalence of Kazachstania spp. Regar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…This indicates that the piglet fecal bacteriome likely follows a defined pattern of colonization and succession in healthy developing piglets, whereas in the mycobiome a large portion of the community may be transient and driven by other factors, such as environmental exposure, diet, or host immunity, which may vary by piglet. Other studies have purported similar hypotheses regarding the transient nature of the mycobiome based on compositional variability among sample subjects and association of fungal genera with food or environmental sources [ 36 , 43 , 44 ]. In the pre-wean piglet mycobiome, environmental influence is suggested by the dominance of naturally ubiquitous fungal families Trichosporonaceae , Mucoraceae , and Cladosporiacea , all of which are found in a variety of environments including organic debris, soils, and indoor/outdoor air [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This indicates that the piglet fecal bacteriome likely follows a defined pattern of colonization and succession in healthy developing piglets, whereas in the mycobiome a large portion of the community may be transient and driven by other factors, such as environmental exposure, diet, or host immunity, which may vary by piglet. Other studies have purported similar hypotheses regarding the transient nature of the mycobiome based on compositional variability among sample subjects and association of fungal genera with food or environmental sources [ 36 , 43 , 44 ]. In the pre-wean piglet mycobiome, environmental influence is suggested by the dominance of naturally ubiquitous fungal families Trichosporonaceae , Mucoraceae , and Cladosporiacea , all of which are found in a variety of environments including organic debris, soils, and indoor/outdoor air [ 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 93%
“…One of the most striking differences included a high level of variation in the relative abundances of fungal families Saccharomycetaceae ( K. slooffiae ) and Debaryomcetaceae ( H. burtonii ). K. slooffiae , a persistent fungus in post-weaned piglets [ 30 , 44 ], is hypothesized to be a potential protein source to healthy pigs [ 14 ] and may behave similarly to commensal Candida species in humans [ 13 ]. In a study on human diets, Candida was positively correlated with high carbohydrate consumption [ 50 ] and has been shown to degrade starches [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, more additional aspects need to be considered. Firstly, in addition to bacteria, the microbial community of pig fecal samples is characterized by other microorganisms, such as yeasts and fungi (Ramayo-Caldas et al, 2020 ). This may have led to discrepancies between the experimental results of functional metabolism detected by the Ecoplates and the prediction analysis on 16S rRNA performed on the bacterial microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Commensal gut populations modulate hosts' immune responses, which in turn can modify the microbiota composition to maintain gut homeostasis [20,21]. Recently, polymorphisms located in immune genes associated with the abundance of microbial communities have been reported [22][23][24][25]. Furthermore, it has been suggested that the pattern recognition receptors, which are proteins capable of recognizing molecules frequently associated with pathogens, may have evolved to mediate the bidirectional crosstalk between microbial symbionts and their hosts [26].…”
Section: Introductionmentioning
confidence: 99%